2007
DOI: 10.1111/j.1462-2920.2007.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Global survey of diversity among environmental saltwater Bacteriovoracaceae

Abstract: Halophilic Bacteriovorax (Bx), formerly known as the marine Bdellovibrio, are Gram-negative, predatory bacteria found in saltwater systems. To assess their genetic diversity and geographical occurrence, the small subunit rRNA (ssu-rRNA) gene sequences were analysed from 111 marine, salt lake and estuarine isolates recovered from 27 locations around the world. Phylogenetic analysis of these isolates using Geobacter as the outgroup revealed eight distinct ribotype clusters each with at least two isolates. Each c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
95
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(105 citation statements)
references
References 40 publications
8
95
0
Order By: Relevance
“…Using full-length 16S analysis, the phylogenetic relatedness of these isolates to other BALOs was inferred ( Figure 1e). Our Halobacteriovorax isolates were all identical at the 16S rRNA sequence level (accession #KR493097), and grouped within the previously established Halobacteriovorax cluster XIII (Figure 1e; Pineiro et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using full-length 16S analysis, the phylogenetic relatedness of these isolates to other BALOs was inferred ( Figure 1e). Our Halobacteriovorax isolates were all identical at the 16S rRNA sequence level (accession #KR493097), and grouped within the previously established Halobacteriovorax cluster XIII (Figure 1e; Pineiro et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to viruses, which are the most abundant biological entity in the marine environment and maintain abundances approximately in an order of magnitude greater than their hosts, BALOs do not need to be in high initial concentrations in the environment to drive significant bacterial mortality of their prey (Richards et al, 2012;Williams et al, 2016). One group of Bdellovibrionales, the marine Halobacteriovorax, are broadly distributed in marine waters across temperature, salinity and pH gradients (Pineiro et al, 2007). Halobacteriovorax predation represents a regulatory mechanism that can alter the structure of bacterial communities (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One approach, comparative analysis of 16S rRNA sequences, has enabled identification and detection of specific Bacteriovorax phylogenetic clusters or operational taxonomic units (OTUs) within populations (Pineiro et al, 2004). This has made possible geographical distribution studies that have found that some OTUs occur widely and in diverse environments; whereas, others are restricted to certain ecosystems (Pineiro et al, 2007). Such findings have advanced knowledge of Bacteriovorax, and raised new questions about environmental parameters that account for the varied distribution patterns of different OTUs.…”
Section: Introductionmentioning
confidence: 98%
“…Such findings have advanced knowledge of Bacteriovorax, and raised new questions about environmental parameters that account for the varied distribution patterns of different OTUs. Salinity and temperature are among such parameters (Williams and Falkler, 1984;Pineiro et al, 2007) and there is speculation on a role for the prey (Sutton and Besant, 1994;Pineiro et al, 2004). In this scenario, different prey species select for distinct populations of Bacteriovorax OTUs, and thereby influence the presence, distribution and services of the predators in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Although relatively low in abundance, typically 0-50 plaque-forming units (PFU) per ml (Taylor et al, 1974;Varon and Shilo, 1980;Richards et al, 2013), compared with viruses, BALOs are ubiquitous globally. They have been isolated from oceans, seas, estuaries, salt lakes, ponds, freshwater systems and soils (Taylor et al, 1974;Williams, 1979;Sutton and Besant, 1994;Pineiro et al, 2004;Davidov et al, 2006;Pineiro et al, 2007). Furthermore, many bacteria, up to 80% of cultivable organisms in estuarine systems, have been reported to be susceptible to predation by BALOs (Rice et al, 1998).…”
Section: Introductionmentioning
confidence: 99%